Gut brain interaction theory reveals gut microbiota mediated neurogenesis and traditional Chinese medicine research strategies - Zhang, Chenxi; Xue, Peng; Zhang, Haiyan; Tan, Chenxi; Zhao, Shiyao; Li, Xudong; Sun, Lihui; Zheng, Huihui; Wang, Jun; Zhang, Baoling; Lang, Weiya (Frontiers in Cellular and Infection Microbiology, 2022)
Adult neurogenesis is the process of differentiation of neural stem cells (NSCs) into neurons and glial cells in certain areas of the adult brain. Defects in neurogenesis can lead to neurodegenerative diseases, mental disorders, and other maladies. This process is directionally regulated by transcription factors, the Wnt and Notch pathway, the extracellular matrix, and various growth factors. External factors like stress, physical exercise, diet, medications, etc., affect neurogenesis and the gut microbiota. The gut microbiota may affect NSCs through vagal, immune and chemical pathways, and other pathways. Traditional Chinese Medicine (TCM) has been proved to affect NSC proliferation and differentiation and can regulate the abundance and metabolites produced by intestinal microorganisms. However, the underlying mechanisms by which these factors regulate neurogenesis through the gut microbiota are not fully understood. In this review, we describe the recent evidence on the role of the gut microbiota in neurogenesis. Moreover, we hypothesize on the characteristics of the gut-brain axis based on bacterial phyla, including microbiota’s metabolites, and neuronal and immune pathways while providing an outlook on TCM’s potential effects on adult neurogenesis by regulating gut microbiota.